2012
DOI: 10.1111/j.2040-0209.2012.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Labour Supply in Post‐Conflict Tajikistan

Abstract: The Conflict, Violence and Development research cluster is part of the Vulnerability and Poverty Reduction team at the Institute of Development Studies. The cluster's main focus is to develop new insights into how people in contexts of conflict and violence live and interact, and what institutions best support them. We use our research findings to inform, identify and develop policies and practices that will strengthen people's efforts to secure their own lives and livelihoods. Email: conflict@ids.ac.uk Web: w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 21 publications
1
26
2
1
Order By: Relevance
“…Although most studies on remittances as cited above reported a positive effect of remittances on economic growth, inequality and poverty reduction, many studies show that they negatively affect the labour supply in recipient countries. These include Justino andShemyakina (2010 and; Hernandez- Coss (2006); Bridi (2005) for the Latin American and Caribbean region; Funkhauser (1992); Chami, Fullenkamp and Jahjah (2005); Pablo, Emmanuel and Frederico (2007); and Narazani (2008) for El-Salvador;Zachariah, Mathew and Irudaya (2001) for Malawi; Rodriguez and Tiongson (2001) for India; Kim (2007) for Jamaica ;Funkhauser (2006) for Nicaragua; Amuedo-Dorantes and Pozo (2005) and Hanson (2007) for Mexico; and Justino and Shemyakina (2012) for Tajikistan. On the other hand, Cox-Edwards and Rodriguez-Oreggia (2006) found no evidence of remittances affecting labour force participation in Mexico, while Drinkwater, Levine and Lotti (2003) found that migration and the resulting remittances can have both positive and negative effects on labour supply and labour market participation decisions in the home country.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Although most studies on remittances as cited above reported a positive effect of remittances on economic growth, inequality and poverty reduction, many studies show that they negatively affect the labour supply in recipient countries. These include Justino andShemyakina (2010 and; Hernandez- Coss (2006); Bridi (2005) for the Latin American and Caribbean region; Funkhauser (1992); Chami, Fullenkamp and Jahjah (2005); Pablo, Emmanuel and Frederico (2007); and Narazani (2008) for El-Salvador;Zachariah, Mathew and Irudaya (2001) for Malawi; Rodriguez and Tiongson (2001) for India; Kim (2007) for Jamaica ;Funkhauser (2006) for Nicaragua; Amuedo-Dorantes and Pozo (2005) and Hanson (2007) for Mexico; and Justino and Shemyakina (2012) for Tajikistan. On the other hand, Cox-Edwards and Rodriguez-Oreggia (2006) found no evidence of remittances affecting labour force participation in Mexico, while Drinkwater, Levine and Lotti (2003) found that migration and the resulting remittances can have both positive and negative effects on labour supply and labour market participation decisions in the home country.…”
Section: Study Backgroundmentioning
confidence: 99%
“…In addition, almost all tend to remit cash back to their relatives left behind (Buckley & Hofmann, 2012;Danzer & Ivaschenko, 2010;Gang et al, 2016;World Bank, 2009). It is widely believed that labour migration and remittance inflows have successfully helped smooth the economic and social impact of the transition away from a planned economy and the subsequent civil unrest (Clément, 2011;International Monetary Fund, 2005;Justino & Shemyakina, 2012;Kireyev, 2006). The World Bank (2011) estimates that between 2003 and 2007 the national poverty headcount fell from 68 percentage to 37 percentage, meaning that more than a million people were lifted out of poverty over the period.…”
Section: Contextmentioning
confidence: 99%
“…The nature of local authorities differs. Conflicts such as the Chad Basin (Roitman, 2001), the Ituri province conflict in the Democratic Republic of the Congo (Vlassenroot and Raeymaekers, 2004), and the onset of the crisis in northern Mali in 2011 all followed similar trajectories where the withering away of the state allowed local elites to replace state authority (Blattman and Miguel, 2010;Justino, 2012;Justino, Brück and Verwimp, 2013;Kalyvas, 2003Kalyvas, , 2008. In parts of Africa and the Middle East, a "rentier political marketplace", as described by de Waal, is a particular challenge (de Waal, 2014).…”
Section: Source: Glenn (2016)mentioning
confidence: 99%
“…There is evidence to show remittances can increase income inequality (Hinojosa Ojeda and Takesh, 2011) and have significant impacts on the labour supply in post-conflict situations (Justino and Shemyakina, 2012). At a macroeconomic level, there is scattered evidence that remittances in developing contexts predominately flow into non-tradable goods, leading to an appreciation of the exchange rate and subsequent hollowing out of manufacturing and other productive sectors of a national economy (sometimes called "Dutch disease").…”
Section: Aggregate Financial Flows To Fragile Contextsmentioning
confidence: 99%